An Economic Analysis of Coal Pricing in Mongolia - Surmaajav, Lkhaakhuu (Technium Social Sciences Journal, 2024)
Coal is a critical export for Mongolia, playing a significant role in the nation’s economy by contributing to GDP and export revenues. This paper provides an economic analysis of coal pricing in Mongolia, examining the primary factors that drive price fluctuations in both domestic and international markets. Key areas of focus include global demand, particularly from neighboring China, transportation costs, government policies, currency exchange rates, and environmental regulations. The paper employs a mixed-method approach, analyzing historical price data alongside policy reviews to identify the challenges and opportunities Mongolia faces in stabilizing coal prices. Global coal demand, especially from China, has a profound effect on Mongolian coal prices, while infrastructure limitations and transportation costs further exacerbate price volatility. Additionally, Mongolia’s coal sector is influenced by international competition, particularly from established exporters like Australia and Indonesia, which benefit from more developed supply chains. This research aims to provide valuable insights for policymakers and stakeholders by offering recommendations on how Mongolia can enhance price stability and strengthen its position in the global coal market. By analyzing the economic forces shaping Mongolian coal prices, the study contributes to broader discussions on resource management and economic sustainability in coal-dependent economies. The findings will aid policymakers in developing strategies that address Mongolia’s infrastructure challenges and ensure the long-term viability of its coal industry in the face of evolving global energy dynamics.